Petrogenetic significance of the eclogites from the Arquía Complex on southwestern Pijao, Central Cordillera (Colombia Andes) (2017)
Eclogites discovered on southwestern Pijao, Central Cordillera (Colombia Andes), are enriched in almandine (Xalm = 0.50-0.58; XFe = 0.69-0.83) and grossular (Xgrs = 0.25-0.30), with lesser amounts of pyrope (Xprp = 0.12-0.23), and relatively low spessartine (Xsps = 0.01-0.05), and the omphacite the contents of jadeite, acmite and augite in the analyzed clinopyroxene are 7.00, 3.19 and 89.80 mol%; XMg= 0.82. The eclogites underwent a clockwise PT trajectory with a post-Ppeak (at 10.5 kbar and 535°C) slight increase of temperature to a maximum (Tpeak) about 8.5 kbar and 575°C and a subsequent cooling during decompression to about 4.5 kbar and 530°C.Geochemical data indicate protoliths that correspond to basalts from normal type mid-ocean ridges (NMORB). All these features suggest that ophiolite remnants are involved in the subduction and final architecture of the Arquía Complex. The progressive convergence led to the formation of the eclogite facies assemblages at the maximum depth in the continental crust. The eclogites reported in this study represent an excellent example of high-pressure metamorphic rocks in orogenic belts, very useful to understanding plate subduction and continent collision processes.